Expatriate selection, training, family issues and repatriation putting theory into best practice for expatriate success in Australia, Singapore and Malaysia - Neilson, George A. (Curtin University, 2002)
For both large and small companies involved in the internationalisation of world-wide markets, the successful management of expatriate assignment is an important part of overseas commercial activities.This investigation was concerned with expatriate management in fifty, multinational and international organisations in Australia, Singapore and Malaysia to contribute to the enhancement of success and reduction of failure of expatriate assignments.Data was collected to heighten the awareness of practitioners and academics to the value of dealing differently with expatriates. In forecasting the value of expatriates and the importance of global trade in the future, it was shown that the most successful companies are those able to identify and select an ample number of appropriate international managers. Where suitable candidates for relocation are not selected, higher than normal turnover occurs.The unique Australasian models developed and tested in this thesis are a direct response to the results of current research and encourage current practice to be less static. resulting in the rate of expatriate failure being reduced substantially.